Quality of Life and Bank Investments of the Population in the Regions of the Russian Federation - R. A. Arshakyan; A. N. Kurbatsky; M. V. Mironenkova (Статистика и экономика)
Improving the living standards of citizens and improving the investment climate are the key benchmarks of any state.The purpose of this study is to analyze the relationship between quality of life and the growth of bank deposits in the regions of Russia.Materials and methods. The integral index of the quality of life of the population of the Russian regions from 2011 to 2021 was assessed using the method of principal components based on blocks of variables reflecting not only material but also spiritual and moral spheres of society. The authors analyzed the presence of correlation between the integral index of the quality of life and the volume of bank deposits. Assuming that the integral index of the quality of life can have a significant impact on the growth of bank deposits, panel data models with fixed and random effects were constructed and analyzed. The data from the Federal State Statistics Service (Rosstat) and from open Russian Internet resources on banking analytics were used in the paper.Results. The paper shows that despite the presence of a stable correlation between the value of the integral index of the quality of life and the estimate of the volume of deposits, the quality of life does not have a significant impact on the growth of bank investments. Regional inflation is expected to have a negative impact on deposit growth.Conclusion. The increase in free cash stimulates the population to choose the most reliable ways of their preservation and multiplication, for example, bank deposits. However, improving the quality of their lives, the population may begin to consider other, albeit less reliable, but perhaps more profitable areas of investment, such as real estate or mutual funds. In addition, today the compensation for deposits in a bank, in respect of which an insured event has occurred, is paid to the depositor in the amount not exceeding 1.4 million rubles, which encourages agents to consider other investment instruments, if the available free cash exceeds the above amount. In conditions when the growth rates of consumer prices exceed the return on deposits, their real return becomes negative, which means that the population will look for alternative ways of investment. Analysis that takes into account different types of investment by regions of the country is currently a difficult task due to the aggregation and non-transparency of this type of data. We also note that the turbulent period starting from 2022, characterized by a sharp increase in interest rates, requires separate consideration.